Translation of Addressing Terms in The Novel This Earth of Mankind - Ardik Ardianto (Deskripsi Bahasa, 2019)
This paper is an attempt to approach the translational stylistics, aiming at identifying the equivalence and translation procedures used in translating the Toer’s authorial style from the Indonesian language to the English language in the novel This Earth of Mankind. A translational stylistics model proposed by Malmkjær was used to contrast the target text (TT) and the source text (ST), primarily focusing on the stylistic shift. Further, as to the model of translation procedures, it specifically employed Vinay and Darbelnet’s methodology for translation. Data used in this study were addressing terms found in two novels, the Indonesian novel Bumi Manusia and its translation This Earth of Mankind. The rigorous analysis demonstrated how the translation of addressing terms involved a wide range of aspects, such as sociocultural and historical values (including social identity and social strata) and power and solidarity relation. Therefore, it raised a number of noteworthy translation issues, i.e., its equivalence, stylistic shift, and translator’s strategies. Through the increasing awareness of ‘cultural turn’ in translation studies, the concept of equivalence is supposedly perceived not as an absolute assessment but as a mediating attempt to accommodate and transpose the inferred or perceived meaning from the ST to the TT as much as possible. However, the findings are not set out to appraise the translator’s ethical attitude, considering the limited data used in this study and numerous factors that are not yet taken into account, e.g. the power play of the translation industry, and culture-mediating agenda in the receiving culture.